The relationship of Human Resources Management practices on job performance in UAE selected bank with the mediating role of employee motivation - Ali, Amna Ahmad Hassan (Tanjong Malim, 2024)
The relationship of Human Resources Management practices on job performance in UAE selected bank with the mediating role of employee motivation by Ali, Amna Ahmad Hassan